P2-S2.23 Measuring the impact of HIV prevention programme on HIV/STI prevalence and condom use in Karnataka: a case-control approach. (10th July 2011) - Prakash, R; Isac, S; Ramesh, B M; Banandur, P; Moses, S; Washington, R; Bhattacharjee, P
Abstract : Background: The important goal of Avahan programme is to reduce HIV transmission among female sex workers (FSWs) and MSM-T by increasing consistent condom use, reducing risk behaviour and timely treatment of sexually transmitted infections. In order to assess the impact of programme exposure on these outcomes, many of the earlier studies have done impact analyses using periodical Integrated Biological and Behavioural Surveys (IBBAs). Since these studies were cross-sectional in nature, they could not give true impact of programme exposure in the absence of a suitable control group. Therefore, the fact that results may have not occurred independently of the intervention, instead reflecting natural trends in HIV/STI prevalence cannot be ruled out. Methods: Using first two rounds of IBBAs conducted during 2005–2006 and 2008–2009 respectively in four districts of Karnataka namely Belgaum, Bellary, Shimoga, and Bangalore, we use Propensity Score Matching (PSM) method to demonstrate the true effect of different components of programme exposure on HIV/STI prevalence and consistent condom use with all partners. By creating a proxy group of controlled individuals (those individuals who are not exposed to programme), PSM method compares the outcome measures with each respective cases who were exposed to programme. Further, Principal Component Analysis (PCA) is used to generate a composite index by combining a set of programme exposure to analyse whether greater access to programme results into to better outcome. Results: Findings suggest that consistent condom use was higher with occasional clients in comparison to the regular clients cutting across all the districts. The consistent condom use was highest with occasional clients and regular partner in Belgaum (about 92 and 78 percent respectively) while lowest in Shimoga (55% and 48% respectively). The extent of condom use increased for both regular and occasional partners from first survey to second one. Result shows that about 12% FSWs in Belgaum reported any STI symptoms whereas it was about more than 9% in rest of the districts. Findings further revealed the fact that greater the access to program, better was the outcome indicators. The application of PSM method clearly suggested the fact that among all the programme indicators contact of the peers with sex workers has significant positive impact on consistent condom use and HIV/STI reduction. Though the prevalence of HIV/STI was less among those sex workers who visited to clinic compared to the other groups, it was not statistically significant. Conclusions: PSM is a better alternative method to analyse the impact of programme response in the absence of a real control group. Findings clearly conclude that Peer-led Outreach "strategy is successful in scaling up HIV prevention programme, nevertheless, focus of peers on motivating key population to clinic may also contribute to HIV/STI reduction and greater condom use."